Chronic giant cranial diploe hematoma in hemophiliac - gong, weizhao; Wang, Hanshi; jiang, taipeng; zuo, dahui (Journal of Neurological Surgery Part A: Central European Neurosurgery)
Cranial diploe hematoma is a hematoma that occurs between the inner and outer layer of the skull and is often in infants and young children. Hemophilia A is an inherited X-linked bleeding disorder caused by a deficiency of coagulation factor VIII (FVIII) . Epidemiological survey results show that the prevalence of hemophilia in 24 provinces and cities in China is 2.73/100,000, while only about 5% of patients are registered . Hemophilia is mainly characterized by bleeding, which can occur anywhere in the pa-tient's body and manifest as intracranial, gastrointestinal, or pharyngeal bleeding, which can be life-threatening in severe cases. This article shares a case of a patient with he-mophilia A complicated by a chronic giant diploe hematoma.